STRATEGIC COMMUNICATION MUSEUM KERETA API AMBARAWA MANAJER KEUANGAN DAN AKUNTANSI - Taufik Reza Ardianto; Djoko Setyabudi; M Bayu Widagdo; Tandiyo Pradekso (Interaksi Online, 2015)
Museum is no longer become the main option by the public to visit. Museum regardedas a boring place when its compared with natural tourist attraction. Visitors could get alot of things at Ambarawa Train Museum, which is one of the three largest trainmuseum in the world. Because of their lack of knowledge, the number of visitors of thismuseum practically very small. For that, this activities carried out.Finance and Accounting Division is a field that manage the financial activities ofStrategic Communication Ambarawa Train Museum. This division is responsible fortransparency, clarity and neatness of the financial statements. Successful performance ofthis division is when the financial account balance from pre, during until post-event, thesmooth of cash flows and all the needs can be fulfilled.Some plans didn’t run properly due to some emerging issues. In the midst of theemergence of the issues, finance and accounting managers are able to develop atransparent and reliable (accountable) finance management. Activities that is not muchcontribute to the objectives of this series of activities, reduced or eliminated altogether.The problems such as delays and uncertainties can be solved by the finance andaccounting manager.Although this activity was in the absence or shortage of funds in the beginning, awhole activities can still be carried out. Until the end of this activities, finance andaccounting managers successfully carry out their duties. Evidenced by the balanced ofbalance sheet and all the needs can be met that make all the activities implemented. Thissuccess is the result of cooperation and coordination with all team members in orderwith all its limitations, and any problems encountered, the main purpose of thisactivities still achieved.